The Effect of Felt Accountability on User Satisfaction with Accounting Information - Dang Anh Tuan (Emerging Science Journal, 2024)
Felt accountability affects an account-givers’ behavior, decisions, and organizational performance. Accounting information (AI) is provided for decision-making and accountability in the public sector. This study investigated the effects of felt accountability on expertise, legitimacy, and AI disclosure level for accountability on users’ satisfaction. Survey data included 401 responses across public institutions in Vietnam, and SEM linear structure analysis was used to examine the results. The research findings indicate that felt accountability directly affects users’ satisfaction and their expertise and legitimacy, and the level of AI disclosure. The expertise and legitimacy of the account-holder and the level of AI disclosure partially mediate the relationship between felt accountability and users’ satisfaction. This implies that AI's needs, purposes, and importance are determined based on hypothetical users that are not useful in reality. In practice, AI must meet accountability requirements to bring satisfaction to users. The satisfaction level of actual users of AI is influenced by the account-givers’ perceived accountability regarding the needs, expertise, and legitimacy of the account-holder. Therefore, it is essential to identify the type of information needed, the timing of AI disclosure, and the actual AI users to reduce the gap between the supply and demand of AI. The research results provide evidence supporting agency and social contingency theories in accountability relationships. Doi: 10.28991/ESJ-2024-08-02-023 Full Text: PDF